Rethinking Longitudinal Research on Canadian Immigrant Health: Methodological Insights, Emerging Challenges, and Future Considerations - Sunmee Kim; Eugena Kwon (Social Sciences)
Longitudinal research provides critical insights into the evolving health trajectories of immigrants, capturing changes from initial arrival through to long-term settlement. However, longitudinal studies on immigrant health in Canada face persistent methodological challenges that limit their impact and policy relevance. This review critically examines 34 peer-reviewed articles, published between 1996 and 2024, that employed longitudinal data to investigate physical and mental health outcomes among Canadian immigrants. We identify key methodological limitations, including a heavy reliance on earlier datasets (71% of studies used data collected between 1994 and 2007), oversimplified outcome measures (e.g., collapsing continuous or Likert-scale variables into dichotomous categories without clear justification), the limited use of appropriate longitudinal methods, and the inadequate handling of missing data. Advancing immigrant health research in Canada will require enhanced data infrastructure, greater methodological rigor, and more transparent reporting practices to better inform evidence-based policy. This review offers researchers and policymakers a clear summary of existing methodological gaps and presents practical strategies to strengthen future longitudinal research on immigrant health in Canada.